2021
DOI: 10.1038/s41467-021-23675-y
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory landscape of Arabidopsis thaliana roots at single-cell resolution

Abstract: The scarcity of accessible sites that are dynamic or cell type-specific in plants may be due in part to tissue heterogeneity in bulk studies. To assess the effects of tissue heterogeneity, we apply single-cell ATAC-seq to Arabidopsis thaliana roots and identify thousands of differentially accessible sites, sufficient to resolve all major cell types of the root. We find that the entirety of a cell’s regulatory landscape and its transcriptome independently capture cell type identity. We leverage this shared info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 49 publications
1
92
0
Order By: Relevance
“…Importantly, single-cell ATAC-seq in plants proved highly effective for the detection of CRMs at single-cell resolution ( Marand et al, 2021 ), allowing the detection of cell-type-specific CRMs, even in lowly abundant cell types. Data from Arabidopsis and maize revealed that approximately one-third of detected ACRs are cell-type specific ( Dorrity et al, 2021 ; Marand et al, 2021 ). Notably, the latter were enriched for TFBSs of TFs expressed in these cells ( Dorrity et al, 2021 ; Marand et al, 2021 ).…”
Section: Identifying and Verifying Crms Individually And Genome-widementioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, single-cell ATAC-seq in plants proved highly effective for the detection of CRMs at single-cell resolution ( Marand et al, 2021 ), allowing the detection of cell-type-specific CRMs, even in lowly abundant cell types. Data from Arabidopsis and maize revealed that approximately one-third of detected ACRs are cell-type specific ( Dorrity et al, 2021 ; Marand et al, 2021 ). Notably, the latter were enriched for TFBSs of TFs expressed in these cells ( Dorrity et al, 2021 ; Marand et al, 2021 ).…”
Section: Identifying and Verifying Crms Individually And Genome-widementioning
confidence: 99%
“…Data from Arabidopsis and maize revealed that approximately one-third of detected ACRs are cell-type specific ( Dorrity et al, 2021 ; Marand et al, 2021 ). Notably, the latter were enriched for TFBSs of TFs expressed in these cells ( Dorrity et al, 2021 ; Marand et al, 2021 ).…”
Section: Identifying and Verifying Crms Individually And Genome-widementioning
confidence: 99%
“…Single-cell sequencing has ushered in a new era of biology where it is possible to characterize cell types and function with unprecedented detail. In plants, this has resulted in detailed single-cell RNA-seq and Assay for Transposase-Accessible Chromatin (scATAC-seq) datasets primarily on different organ types from well-studied model organisms ( Denyer et al, 2019 ; Ryu et al, 2019 ; Dorrity et al, 2021 ; Gujas et al, 2020 ; Marand et al, 2020 ; Song et al, 2020 ; Liu et al, 2020a , 2020b ; Chen et al, 2021 ; Lopez-Anido et al, 2021 ; Xu et al, 2021 ). Most plant studies to date start with protoplast isolation, which has the potential to miss some recalcitrant cell types and often require correction to control for transcriptional changes elicited by lengthy enzyme treatment and centrifugation steps ( Ryu et al, 2019 ; Cuperus, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent development of droplet microfluidic device-based single-cell systems have enabled researchers to co-encapsulate individual cells or nuclei with barcode beads in nanoliter water-inoil emulsions, making it possible to perform sequencing at the single-cell level (Lareau et al, 2019;Satpathy et al, 2019). For example, single-cell ATAC-seq (scATAC-seq) assays based on the 10X Genomics Chromium system have been successfully applied to study cell-specific chromatin accessibility in plants (Dorrity et al, 2021;Farmer et al, 2021;Marand et al, 2021;Marand and Schmitz, 2022). However, these commercial single-cell assays often require specialized equipment, trained personnel, and are very expensive, making it difficult for an individual laboratory to perform in house.…”
Section: Introductionmentioning
confidence: 99%